On the exchange rate between the Deutsche Mark and the Swiss Franc: An empirical investigation - Reinhard Fürstenberg (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1982)
This is an empirical study on the exchange rate between the Swiss Franc and the Deutsche Mark. We are using a priori theoretical reasoning in order to determine a set of variables which appear capable of explaining real exchange rate changes. These variables may themselves be to some extent determined by changes in the exchange rate. A priori, the direction of causality is left open and brought to our knowledge by a search process for Granger-causality among this set of variables. This study tries to back up or refute, as the case may arrive, pieces of economic theory. We consider the theory of measurement, the methodology of measurement and the data as given for the time being. Any result that may be obtained in this way is thus limited in its stability as it is valid only relative to the above implicit assumptions.
Keywords: 330